(untitled) (Academicia Globe: Inderscience Research, 2021)
The paper deals with the state and directions of Internet usage in the educational system of Uzbekistan. Questions about the main advantage of Internet usage in the educational system, particularly in higher education institutions of Uzbekistan are analyzed. In this article you can learn about a number of advantages of the proposed directions, which can use the listed opportunities of the Internet, new technologies that open up large and largely unexplored opportunities for education development. The article deals with the main advantage of distance education, which in turn is defined as learning with the help of information and communication technologies (ICT).